Therapeutic Potential of Alpinia officinarum - Pillai, Manoharan K.; Young, David J.; Bin Hj Abdul Majid, Hj Mohamed (Mini Reviews in Medicinal Chemistry, 2018)
The plant Alpinia officinarum of the ginger family originated in China and is used throughout South and South-East Asian countries to flavor food and as a traditional medicine to treat a variety of diseases. This review summarizes the biological, pharmacological and phytochemical properties of extracts and subsequently isolated compounds from A. officinarum. In vitro and in vivo studies of both extracts and pure compounds indicate a wide variety of potent bioactivities including antiinflammatory, antibacterial, antioxidant, antiobesity, anticancer, enzyme inhibitory and remarkable antiviral properties. The latter is particularly promising in the face of emerging, virulent respiratory diseases in Asia and the Middle East.
Keywords: In vitro